2020
DOI: 10.1556/650.2020.31796
|View full text |Cite
|
Sign up to set email alerts
|

A kiégés előfordulása szociális munkások körében

Abstract: Összefoglaló. Bevezetés: Napjaink egyik legszélesebb körben emlegetett jelensége a kiégés (burnout), mely a leggyakrabban a segítő szakmákban dolgozókat érinti. Célkitűzés: Munkánk célja a kiégés jelenségének komplex vizsgálata szociális munkások körében. Módszerek: A demográfiai adatok felvétele mellett a kiégés vizsgálatához a Maslach Burnout Inventory (MBI) kérdőívet használtuk, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 20 publications
2
8
0
5
Order By: Relevance
“…Our findings suggest that burnout is indeed a serious problem for social workers today, with a quarter of the sample investigated (N=83) affected by high levels of burnout (25.3%), nearly one half (44.6%) scored in a range that indicate a medium / moderate level of burnout and almost one third (30.1%) reported low levels of burnout. In line with our study, in the range of moderate to high and severe levels of burnout are reported about 60% of social workers [30,32], even before the pandemic outbreak. A study that examined COVID-19 related peritraumatic distress (the physiological and/or emotional distress experienced by an individual during a traumatic event) among child welfare workers (N=1996) in US indicating that nearly half of all participants (46.4%) scored in a range indicating mild or severe peritraumatic distress that may lead to professional burnout as the authors state [4].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings suggest that burnout is indeed a serious problem for social workers today, with a quarter of the sample investigated (N=83) affected by high levels of burnout (25.3%), nearly one half (44.6%) scored in a range that indicate a medium / moderate level of burnout and almost one third (30.1%) reported low levels of burnout. In line with our study, in the range of moderate to high and severe levels of burnout are reported about 60% of social workers [30,32], even before the pandemic outbreak. A study that examined COVID-19 related peritraumatic distress (the physiological and/or emotional distress experienced by an individual during a traumatic event) among child welfare workers (N=1996) in US indicating that nearly half of all participants (46.4%) scored in a range indicating mild or severe peritraumatic distress that may lead to professional burnout as the authors state [4].…”
Section: Discussionsupporting
confidence: 92%
“…The main stressors related to the work environment identified in our study and found in other studies are: increased workload [18,26,27,31,48], lack of material / financial resources to support more beneficiaries, new rules and decisions at national level [10,27] associated with inconsistency, instability, ambiguity of decisions, sudden changes or even their absence or non-assumption at the managerial level [27,30], lack of clarity of working procedures [10,26]; lack of support from the management of the institution [26,31,[48][49][50]. High job demands and low resources are known to be the primary reasons for burnout [51].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Previous research has shown that social workers are a profession at high risk for developing burnout syndrome [37,[43][44][45][46][47][48][49]. For the employees who work in this field, studies have repeatedly shown that those experiencing burnout have undergone long periods of work-related stress and job demands [50].…”
Section: Job Stress and Burnout Among Social Workersmentioning
confidence: 99%